Ocular injuries in a paediatric population at a child eye health tertiary facility, Ibadan, Nigeria (2023)
Purpose: To determine the pattern, causes and risk factors for ocular injuries amongst children presenting to a tertiary facility in Ibadan, southwest Nigeria Methods: A retrospective review of clinical records of patients aged 16 years and below who presented with ocular injuries to the eye emergency unit between May 2010 and April 2016. Information extracted includes patient’s demography, location and circumstances of injury, clinical findings, and management. Data was analysed using IBM SPSS Statistics for Windows, Version 26.0. Descriptive and inferential statis- tics were calculated. Odds ratio were derived from regression models adjusted for confounders. Significance was set at a P-value of 0.05. Results: A total of 109 children were studied. Majority were boys (male to female ratio = 2.9:1). The median age at presentation was 9 years. Injury occurred at home in 67 (61.5%) children, and at school in 30 (27.5%). More than half of the children were injured during play, 18 (16.5%) during corporal punishment, and 34 (31.2%) by accidents during domestic/schoolwork. Majority (73.4%) were closed globe injuries. The odds of injury with sharp objects and ocular trauma score of 4 or less was were 3.2 times (95% Confidence interval CI: 1.3–7.7) and 3.9 times (95% CI:1.4–11.4) higher in children aged 0–5 years respectively. The odds of open globe injury was 9.8 times (95% CI: 3.4–28.6) higher in injury from sharp objects. Wood/stick, cane, stone, broomstick and fist/palm/finger were the agents responsible for two- thirds of injuries. Conclusion: This study revealed that children predominantly sustain ocular injuries at home and younger children have greater odds of severe injuries with profound implications for visual disability. Health education, adult supervision and the application of appropriate measures necessary for reducing the incidence and severity of childhood ocular trauma are advocated.